2020
DOI: 10.1186/s12891-020-03309-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect and potential risks of using multilevel cement-augmented pedicle screw fixation in osteoporotic spine with lumbar degenerative disease

Abstract: Background: The increase of augmented level and bone cement dose are accompanied by the rising incidence of cement leakage (CL) of cement-augmented pedicle screw instrumentation (CAPSI). But the effect and potential risks of the application of CAPSI to osteoporotic lumbar degenerative disease (LDD) have not been studied in the case of multilevel fixation. This study aimed to investigate the effectiveness and potential complications of using multilevel CAPSI for patients with osteoporotic LDD. Methods: A total … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
0
22
1
1
Order By: Relevance
“…Sixteen studies reported data on cement leakage [16,18,21,[27][28][29][30][31][32][33]56,[59][60][61][62][63] (Table 4 and Figure 5), 7 of which reported the number of patients who developed cement leakage with pooled prevalence of 34.36% (95% CI: 1.81%, 66.91%) [18,[27][28][29][30]59,60]. These studies exhibited high heterogeneity (I 2 = 99%; p < 0.0001).…”
Section: Cement Leakagementioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen studies reported data on cement leakage [16,18,21,[27][28][29][30][31][32][33]56,[59][60][61][62][63] (Table 4 and Figure 5), 7 of which reported the number of patients who developed cement leakage with pooled prevalence of 34.36% (95% CI: 1.81%, 66.91%) [18,[27][28][29][30]59,60]. These studies exhibited high heterogeneity (I 2 = 99%; p < 0.0001).…”
Section: Cement Leakagementioning
confidence: 99%
“…The other secondary outcomes of our study (fusion rate, pulmonary embolism, proximal junctional kyphosis, infections) had less than 3 distinct data points in each group and pooled estimates for these outcomes were therefore not calculated. Fusion rates were reported in four studies [16,59,62,63], with only one comparative study showing higher rate for augmented FPS. Pulmonary embolism rate was reported in six studies [27,28,30,31,60,62], indicating a relatively low rate varying from zero to 4.65% in all studies.…”
Section: Other Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these methods all have their limitations. Bone cement leakage is a common complication of bone cement augmented screws, with a leakage rate of 11.6-82.4%, which can cause serious complications such as nerve injury, vascular injury, pulmonary cement embolism, cardiac embolism and anaphylactic shock 23 . In CBT, screws are inserted through the isthmus, and the screws can only be inserted into the posterior 1/3 of the vertebral body.…”
Section: Discussionmentioning
confidence: 99%
“…Polymethylmethacrylate (PMMA) bone cement improves immediate stability and increases pullout resistance from 173% to 244% for patients with osteoporosis undergoing thoracic fracture transpedicular fixation. [ 4 , 14 , 19 ]…”
Section: Introductionmentioning
confidence: 99%